Mitochondrial co-chaperone protein Tid1 is required for energy homeostasis during skeletal myogenesis. Issue 1 (December 2016) - Cheng, Li-Hao; Hung, Kai-Feng; Lee, Te-Chang; Huang, Chih-Yang; Chiu, Wen-Ting; Lo, Jeng-Fan; Huang, Tung-Fu
Abstract Background Tid1 is a mitochondrial co-chaperone protein and its transcript is abundantly expressed in skeletal muscle tissues. However, the physiological function of Tid1 during skeletal myogenesis remains unclear. Methods In vitro induced differentiation assay of mouse myoblast C2C12 cells was applied to examine the physiological role of Tid1 during skeletal myogenesis. In addition, transgenic mice with muscle specific (HSA-Cre) Tid1 deletion were established and examined to determine the physiological function of Tid1 during skeletal muscle development in vivo. Results Expression of Tid1 protein was upregulated in the differentiated C2C12 cells, and the HSA-Tid1f/f mice displayed muscular dystrophic phenotype. The expression of myosin heavy chain (MyHC), the protein served as the muscular development marker, was reduced in HSA-Tid1f/f mice at postnatal day (P)5 and P8. The protein levels of ATP sensor (p-AMPK) and mitochondrial biogenesis protein (PGC-1α) were also significantly reduced in HSA-Tid1f/f mice. Moreover, Tid1 deficiency induced apoptotic marker Caspase-3 in muscle tissues of HSA-Tid1f/f mice. Consistent with the in vivo finding, we observed that downregulation of Tid1 not only reduced the ATP production but also abolished the differentiation ability of C2C12 cells by impairing the mitochondrial activity. Conclusion Together, our results suggest that Tid1 deficiency reduces ATP production and abolishes mitochondrial activity, resulting in energy imbalance and promoting apoptosis of muscle cells during myogenesis. It will be of importance to understand the function ofTid1 during human muscular dystrophy in the future.